Pemetaan Ergonomi pada Proses Pembuatan Batik - Rofiatun Rofiatun; Mubasysyir Hasanbasri (Health Sciences and Pharmacy Journal, 2018)
The use of non-standard work equipment, inadequate working environment, and health conditions that are poorly monitored by health services are a problem experienced by workers in the informal sector. Ergonomic risks arising from faulty work positions, unsafe workplaces and low knowledge of occupational safety and health. The process of making batik done manually, with long working hours and work postures that are not safe and comfortable. This study aimed to analyze the work posture with the level of ergonomic risk in the batik home-based  worker as well as preventive and promotive efforts made by health workers. The research was conducted qualitatively, with in-depth interview method and observation. Triangulation is done to obtain objective information. The ergonomic risk level analysis is done using the Rapid Entire Body Assessment (REBA) method. measurement of work posture done in batik making process obtained REBA score as follows, score 2-4 for waxing or nyanthing, score 7 for coloring process, score 4 and 8 for rinsing process and score 5 for process wax release. Ergonomic risk in the process of batik in the category of medium, medium category for colouring, medium and high category for rinsing process, and medium category for wax release, and still low preventive and promotive efforts made by health workers.